Relation between pulmonary function changes and diaphragmatic ultrasound in patients with idiopathic pulmonary fibrosis - Alaa Ahmed Ibrahim; Aya Mohamed Mohamed Abd-Eldayem; Hossam Eldin Mohamed Abdel Hamid (The Egyptian Journal of Bronchology)
Abstract Background IPF is a chronic disease with impaired diaphragmatic function. In the vast majority of patients, lung function gradually deteriorates until intractable respiratory failure occurs. Aim of work To assess diaphragmatic ultrasound in IPF patients and its relation to functional parameters. Subjects and methods This study used a case–control design and involved IPF patients who were either attending an outpatient clinic or admitted to a ward at Ain Shams University Hospitals and Abbassia Chest Hospital. Forty-five participants were included and split up into 3 groups: group A: 15 IPF cases suffering from hypoxia. Group B: 15 IPF patients without hypoxia or respiratory failure. Group C: 15 healthy participants as controls. Result Groups A and B had considerably decreased diaphragm excursion (QB), thickness of diaphragm at the end of inspiration, diaphragm thickness fraction, and diaphragm thickness fraction % when compared to the control group. Patients' diaphragm excursion during deep breathing was significantly smaller in group A than it was in the controls. The diaphragm excursion (QB and DB), the thickness of the diaphragm at the end of inspiration, the thickness fraction, and the fraction % were positively associated with FVC, FEF 25–75, FEV1, 6MWT, the O2 sat before, the O2 sat after, and the O2 at RA, while they were negatively correlated with FEV1/FVC. There was no difference between groups in diaphragm thickness at the end of expiration. Conclusion Diaphragmatic ultrasound parameters demonstrated strong correlations with pulmonary function parameters, 6-min walk test, and oxygen saturation levels.